Experience with long-term infliximab therapy in patients with ankylosing spondylitis - Oksana Alekseevna Rumyantseva; A G Bochkova; K Kh Kuzikyants; A V Levshakova; Sh F Erdes; E L Nasonov; Oksana Alekseyevna Rumyantseva; A G Bochkova; K Kh Kuzikyants; A V Levshakova; Sh F Erdes; E L Nasonov (Научно-практическая ревматология, 2010)
The duration of continuous use of infliximab is more than 8 years in patients with ankylosing spondylitis (AS). The efficiency of the drug persists in most patients during its long-term regular therapy. Objective. To evaluate the effectiveness and safety of long-term infliximab therapy in patients with AS, particularly in those with a treatment interruption of ≥16 weeks, and to analyze the effect of the drug on various clinical manifestations of AS. Subjects and methods. The follow-up included 62 patients with a valid diagnosis of AS (New York criteria 1984) who received long-term (≥1 year) regular infliximab therapy in the Anticytokine Therapy Room, Research Institute of Rheumatology, Russian Academy of Medical Sciences. The dose of infliximab was 5 mg/kg. The following parameters: BASDAI and BASFI indices, global AS activity, the number of inflamed joints, enthesitis, and erythrocyte sedimentation rate were estimated in all the patients before therapy and each infusion. Improvement was determined by the ASAS criteria. Effectiveness was ascertained based on the maximum ASAS improvement that was observed per at least 75% of visits. Account was taken of the following clinical manifestations of AS: spondylitis, peripheral arthritis, coxitis, dactylitis, heel enthesitis, psoriasis, and inflammatory bowel diseases. A subgroup of 17 patients who had a forced increase in infliximab infusion intervals from 16 weeks to 3 years was separately identified in the study group. Results. The mean age of all the patients was 32.7 years; the mean duration of AS was 13.4 years; the mean therapy duration was 2.5 years. The therapy was performed for more than 3 and more than 5 years in 13 and 22 patients, respectively. According to therapy response, all the patients were divided into 3 groups: 1) those with ASAS improvement; 2) those with partial remission; 3) those with secondary inefficiency. Partial remission was observed in 35 (57%) patients; ASAS 40 improvement was seen in 15 (24%); secondary inefficiency developed in 12 (19%) patients. Peripheral arthritis was significantly less common in the group of patients who had achieved partial remission versus those who had achieved 40% improvement and those who had developed secondary inefficiency (p < 0.05, Fisher's exact test). The reasons for a time break in therapy with infliximab were the absence of the drug (n = 11), Mantoux test conversion (n = 2), pregnancy (n = 2), adverse events (n = 2). The mean therapy break was 20.7 (range 16-144) weeks. After therapy resumption, persistent efficacy of infliximab remained in all the patients. During the first infusion after interruption, all the patients were given premedication with the H1- histamine receptor blocker cetirizine in a dose of 10 mg/day and 10 patients received additionally glucocorticoid (GC) premedication. Infusion reactions were observed in 4 (24%) patients during the second (after interruption) infusion without GC premedication. Infliximab was discontinued because of infusion reactions in 2 (12%) of these patients. Conclusion. The majority of patients with AS could achieve persistent partial remission during long-term infliximab therapy. Secondary infliximab inefficacy occurred more commonly in patients with peripheral arthritis. When the treatment was forcedly interrupted, the efficacy of infliximab after therapy resumption was not decreased and its tolerability became slightly worse - infusion reactions were seen in 24% of the patients; 12% required infliximab to be discontinued because of infusion reactions. When therapy is resumed after its > 16- week interruption, it is expedient to use cetirizine for 5 days and/or premedication with GC (prednisolone in a dose of 50 mg or dexaven in a dose of 8 mg).